Financial Feasibility of Citronella in The Reforestation Area - Suryadi Suryadi; Riani Riani; Jamilah Jamilah; Emmia Tambarta Kembaren (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2022)
Sawang District in North Aceh Regency, has a large forest area. During the sustained conflict in Aceh, most of forest areas were degraded and greatly affected the destruction of the forest ecosystem. The citronella plants on reforestation land have a high potential to be developed as intercropping plant because have a high economic value and could be cultivated during 5-7 years. The research is located in Riseh Tunong Village, Sawang District, North Aceh. This research was conducted from July to October 2022. The data was obtained using direct interviews with farmers who maintain forest reforestation with various annual plants and also cultivated citronella plants as intercropping plant. The population in this study were all farmers who cultivate citronella as intercropping plant in reforestation area. The respondents is amount 15 farmer. The financial feasibility analysis of citronella is showed that this comudity is very feasible to be cultivated on reforestation land in North Aceh Regency. The results of the financial feasibility analysis obtained that the NPV value is amount IDR. 43,179,262 which > 0, Net B/C value amount 2.54 which > 0, The acquisition IRR value is amount 57,44% which bigger than interest rates (10%). This research shows that the potential to develop citronella commodity is classified as very feasible. Communities can carry out forest and still get additional income from citronella commodities which have high economic value